Comparative Advantage: Conception, Formulation, and Implications - Rassekh, Farhad (Journal of Knowledge Management Practice, 2026)
The theory of comparative advantage – generally recognized as a central proposition in economics – spawns several implications that are paramount for economic relationships across economies and business firms. The implications are rooted in the history of its development. This paper presents the conception, formulation, and extension of comparative advantage while explicating its implications. The paper also (selectively) cites the empirical literature on the static and dynamic gains from trade as they relate to comparative advantage.